IMPLEMENTATION OF THE RAMSAR CONVENTION ON THE CONVERSION OF MANGROVE LAND IN COASTAL AREAS OF SOUTH SULAWESI (Proceeding of SINERGY, 2026)
The purpose of the international Ramsar Convention is to prevent, control, and stop the destruction of mangrove areas in various coastal areas, both internationally, nationally, and locally. The type of research used is normative, namely examining the normative elements in the Ramsar Convention regarding various cases of conversion of mangrove land in the South Sulawesi Coast. The approach used is a legal approach. Various cases of conversion of mangrove land are mostly dominated by cases of conversion into fishponds by local communities themselves who have long lived in the mangrove areas of the South Sulawesi Coast, such as Maros, Pangkep, Takalar, Jeneponto, Pinrang, and Luwu. Based on the findings and data that have been presented, the application of the most appropriate management concept to control the conversion of mangrove land in the South Sulawesi coastal area is to consistently implement the principles mandated in the Ramsar Convention. The first principle of the Ramsar Convention is the concept of wise use. The second principle of the Ramsar Convention is the obligation to maintain the ecological character of wetlands. The third principle is the concept of conservation combined with sustainable use. The fourth principle is an integrated approach to policy and governance. The fifth principle is community and stakeholder involvement. As an ideal way to resolve the conversion of mangrove land in the coastal areas of South Sulawesi, the five principles of the Ramsar Convention must be implemented.